JALR. New Journal, Old questions, Fresh insights - Paganelli, Roberto (Journal of Alzheimer's Research and Therapy, 2017)
This editorial for the Journal of Alzheimers Research and Therapy outlines persistent questions in Alzheimer biology and care, and highlights emerging tools and study designs. The journal aims to connect mechanistic insight with therapeutic development and practice. It invites interdisciplinary work to accelerate translation and improve outcomes for patients and caregivers.
Keywords: Alzheimer's; dementia; AD risk; antibodies